Factors Related to Mothers' Active Visiting Behavior to Posyandu - Adolfina Merlina Hindom; Indanah Indanah; Muhammad Ridwanto (Indonesian Journal of Global Health Research, 2026)
The low level of mothers' attendance at integrated health posts (Posyandu) in the Sekban Community Health Center of Fakfak Regency indicates suboptimal utilization of basic community health services. This study aims to analyze factors associated with mothers' attendance at Posyandu, including education, age, knowledge of Posyandu, motivation, family support, and distance to Posyandu in the Sekban Community Health Center of Fakfak Regency in 2025. A cross-sectional study was conducted in June–July 2025, in the Sekban Community Health Center of Fakfak Regency. A sample of 101 respondents selected in this study. The dependent variable was mothers' active participation in Posyandu visits. The independent variables were education, age, maternal knowledge, motivation, family support, and distance to the Posyandu. Data collection using a questionnaire, as well as documentation from Posyandu (Integrated Service Post) records. Data analysis was rlogistic regression. The factors that significantly influenced Posyandu activity were motivation (p = 0.020) and education (p = 0.043). Knowledge (p = 0.132), family support (p = 0.445), distance to health facilities (p = 0.053), and age (p = 0.070) did not show a significant effect. The factors that significantly influenced Posyandu activity were motivation and education.